Respostas
respondido por:
0
X ( x-2) + 3x .(2x + 5 ) = 0x² - 2x + 6x² + 15x = 0
x² + 6x² - 2x + 15x = 0
7x² + 13x = 0
Equação do 2º incompleta, vamos fatorar a equação:
x(7x + 13) = 0
x' = 0
7x + 13 = 0
7x = - 13
x = - 13 /7
Resposta: S{ - 13/7 e 0 }
x² + 6x² - 2x + 15x = 0
7x² + 13x = 0
Equação do 2º incompleta, vamos fatorar a equação:
x(7x + 13) = 0
x' = 0
7x + 13 = 0
7x = - 13
x = - 13 /7
Resposta: S{ - 13/7 e 0 }
respondido por:
0
é uma simples equação do segundo grau espero ter ajudado!
Anexos:
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás